Bakhtin on Hearing God's Voice - Slater, Peter (Modern theology, 2007)
Bakhtin's dialogical (not dialectical) philosophy of the everyday, double-voiced prosaic and poetic discourse of asymmetrically interrelated, embodied selves, each answerable to others and the world, found liberating wisdom in modern novelizing texts, notably those of Rabelais and Dostoevsky, with the Chalcedonian Christ prototype as background. He suggests how language is used in Christian contexts by attending to different voices in confessional utterances that may include God's voice/an interlocutory infinite "third"—heard in and through others’ voices—without collapsing perspectival pluralism into relativism. Current work on comparative theology, contrasted with old-style comparative religion, echoes his insights.